Use of diets with Moringa oleifera forage meal for White Leghorn L33 laying hens and replacement pullets - Mesa, O.; Valdivié, M.; Rodríguez, Bárbara; Rabello, C. B.; Berrio, I.; Couso, Zulima (Cuban Journal of Agricultural Science, 2020)
In order to include levels of Moringa oleifera forage meal in diets for White Leghorn L33 replacement pullets (9 to 18 weeks old) and laying hens (19 to 26 weeks old), two experiments were performed. In experiment 1, 0, 10, 15 and 20 % of moringa forage meal was used in the diet for replacement pullets. These animals were randomly distributed, according to a completely randomized design in four treatments with six repetitions each. They received food and water ad libitum. Food intake, food conversion, tarsus length, live weight and organs (ovary, oviduct and liver) weight from 9 to 18 weeks of age showed no differences (P <0.05) among treatments. Abdominal fat deposition was reduced in treatments with 15 and 20 %. In experiment 2, fowls from control and treatment with 20 % of experiment 1 were used. In week 26, hens consuming 20 % of moringa presented similar productive indicators to control treatment, with increased yolk pigmentation. For L33 replacement pullets, from 9 to 18 weeks of age, the use of up to 20% of Moringa oleifera forage meal in diets did not affect growth, productive performance, nor development of ovaries and oviduct. In L33 laying hens, 19 weeks old, the use of 20 % of Moringa oleifera forage meal in diets allowed reaching the laying peak at 26 weeks of age. Keywords: food, trees, Moringa oleifera, replacement pullets